2016
DOI: 10.1016/j.energy.2015.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the predicted effect of passive climate adaptation measures on energy demand for cooling and heating in a residential building

Abstract: Both new and existing buildings need to be adapted to climate change, in order to keep providing a comfortable and healthy indoor climate. Preferably, the adaptation measures applied at the building level scale do not require additional energy (i.e. passive measures). Previous studies showed that passive climate change adaptation measures can have a positive effect on thermal comfort in summer and its shoulder seasons in non-air-conditioned residential buildings. In this paper, the effect of these passive clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 47 publications
(56 reference statements)
2
57
0
9
Order By: Relevance
“…Analysing the literature on that topic, it was observed that generally the energy performance of buildings, aimed at the future projection of energy consumption was carried out using dynamic simulation. In many papers [6,9,16] the simulation was performed using leading software (e.g., TRNSYS, EnergyPlus); in other projects the simulation was performed by calculation procedures developed in-house, [7,[42][43][44] validating those outcomes by a direct comparison with the aforementioned tools.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysing the literature on that topic, it was observed that generally the energy performance of buildings, aimed at the future projection of energy consumption was carried out using dynamic simulation. In many papers [6,9,16] the simulation was performed using leading software (e.g., TRNSYS, EnergyPlus); in other projects the simulation was performed by calculation procedures developed in-house, [7,[42][43][44] validating those outcomes by a direct comparison with the aforementioned tools.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the building stock of three different large Swedish cities (i.e., Stockholm, Lund, and Gothenburg) were considered for carrying out the analysis. Thus, the authors in [9] investigated on the suitability of passive climate adaptation measures for reducing the building energy demand associated to both heating and cooling purposes in the residential sector. In that work, a representative terraced house in the Netherlands was used for all the assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Natural ventilation is one of the most effective passive strategies for improving efficiency and energy saving [33,34], since it requires no energy to operate. Gil-Baez et al [12] assessed the effectiveness of a cross natural ventilation system in a school in southern Spain.…”
Section: Introductionmentioning
confidence: 99%
“…For highly-insulated buildings, heat (e.g. solar radiation through the windows) is trapped inside the building that, as opposed to the case of low-insulated buildings, cannot be transferred easily through the building envelope to the outside environment (van Hooff et al 2016). The accumulation of the heat is further enhanced with the increase of building dimensions, and consequently of the building compactness ratio decrease (Fig.…”
Section: Space Cooling Demandmentioning
confidence: 99%